Estudio inmobiliario de Torrejón de Ardoz - Roch Peña, Fernando; González González, Francisco J.; Pérez Muinelo, Ana (Cuadernos de Investigación Urbanística, 1999)
El estudio que se presenta aquí, realizado como documento de apoyo para el planeamiento del núcleo de Torrejón, describe las condiciones en las que opera la máquina inmobiliaria en un municipio de la corona metropolitana de Madrid, y su relación con los procesos de diferenciación social en este universo local dominado por la vivienda en propiedad. El trabajo muestra cómo la actividad inmobiliaria transforma espacios maduros que nacieron con una gran homogeneidad social, creando nuevos espacios de "calidad" que se auto excluyen, mientras aumenta el parque de viviendas vacías y los viejos tejidos de los años 60 y 70 se degradan y amenazan con convertirse en lugares de marginación. La necesidad de corregir estos procesos abre un campo específico para la política urbanística local a través del planeamiento y la gestión. Abstract: This paper -presented as document to help in the Torrejón city centre planning process- describes the circumstances in which the property developer machine works in a township of the metropolitan area of Madrid, as well as its relation with the processes of social differentiation in this context ruled by the self owned housing. This study shows how property developer activity changes spaces created with social homogeneous into new "good quality spaces" intentionally self excluded, whilst the number of empty houses increases and old 60’s and 70’s districts decline threatening to become social exclusion areas. New "good quality spaces" intentionally self excluded appear into spaces which were in its origin socially homogeneous, meanwhile the amount of empty houses increases and the old districts of the 60’s and 70’s decline threatening become areas of social exclusion. The need of correcting these processes opens a specific opportunity for the local urban policy through planning and management.